Refleksi Eksistensialisme dalam Kesederhanaan: Analisis Karakter pada Film Perfect Days - Binasir, Bahar (Jurnal Ilmiah Multimedia dan Komunikasi, 2024)
This research focuses on analyzing the character of Hirayama in the film Perfect Days (2023) by Wim Wenders through the lens of existentialist philosophy. Utilizing a qualitative method, particularly narrative and character analysis, this research explores how Hirayama’s simple routines and minimalist actions reflect existential themes, such as alienation, individual freedom, and the search for meaning in life. The film employs a minimalist visual style, using techniques such as framing and deep-focus photography to emphasize Hirayama’s emotional isolation and reflective journey. The study reveals that Perfect Days offers a philosophical reflection on how simple daily routines can serve as a medium for existential introspection, in line with the existentialist ideas proposed by Jean-Paul Sartre and Martin Heidegger. This research provides academic value by expanding discussions on existentialism in contemporary cinema and offers practical insights for filmmakers in exploring philosophical themes through a simple yet profound cinematic approach, as well as for audiences in understanding philosophical messages conveyed through narrative and visual elements.